PENGARUH NET PROFIT MARGIN DAN RETURN ON ASSET TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR FARMASI 2017-2019 - Harlyn L. Siagian; Teddy M. Siburian (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2021)
The stock price movement indicates that the company's performance is increasing. Stock prices that are stable and tend to increase will attract investors to join in owning these shares. This study was conducted to determine the effect of net profit margin and return on assets on stock prices in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2017-2019. The population in this study is the financial statements of ten pharmaceutical companies and the sample for this study is financial reports for the years 2017-2019. The sampling method was purposive sampling with criteria or conditions, in order to obtain a total sample of 21 from seven companies that met the criteria. The results showed that the net profit margin and return on assets had an effect on stock prices both partially and simultaneously, where F count> F table.